2003
DOI: 10.1074/jbc.m212659200
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Enhances Adenylyl Cyclase Signaling via Ca2+/Calmodulin

Abstract: Cardiac fibroblasts regulate formation of extracellular matrix in the heart, playing key roles in cardiac remodeling and hypertrophy. In this study, we sought to characterize cross-talk between G q and G s signaling pathways and its impact on modulating collagen synthesis by cardiac fibroblasts. Angiotensin II (ANG II) activates cell proliferation and collagen synthesis but also potentiates cyclic AMP (cAMP) production stimulated by ␤-adrenergic receptors (␤-AR). The potentiation of ␤-AR-stimulated cAMP produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(27 citation statements)
references
References 37 publications
(30 reference statements)
2
25
0
Order By: Relevance
“…Assays were terminated by aspiration of media and addition of 250 l of ice-cold trichloroacetic acid (7.5%) to each well. RIA was used to quantitate cAMP (14,17); results were normalized to the amount of protein per sample, as determined by a colorimetric protein assay (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Assays were terminated by aspiration of media and addition of 250 l of ice-cold trichloroacetic acid (7.5%) to each well. RIA was used to quantitate cAMP (14,17); results were normalized to the amount of protein per sample, as determined by a colorimetric protein assay (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…We used an adenoviral vector to enhance expression in CF of AC6, an AC isoform expressed natively at relatively high levels (14). Basal cAMP levels did not differ between LacZ-and AC6-overexpressing CF (Fig.…”
Section: Ac6 Overexpression Enhances Forskolin-and Adrenomedullin-stimentioning
confidence: 99%
See 1 more Smart Citation
“…AC5/6 Localizes with cav-1 throughout the Cell Membrane and with Phospho-cav-1 at FA Sites-AC5/6 is predominantly detected in buoyant/caveolar membrane fractions, but a portion of AC5/6 localizes in heavy/non-caveolar membrane fractions in cardiac cells (31,32). Immunohistochemical analysis and quantification of AC5/6 and phospho-cav-1 staining of CF revealed that, in addition to being distributed with cav-1 throughout the plasma membrane, 17 Ϯ 4% of AC 5/6 colocalizes with phospho-cav-1 and 57 Ϯ 12% of phospho-cav-1 colocalizes with AC 5/6 at FA sites ( Fig.…”
Section: Phospho-cav-1 Localizes At Fa Sites Independent Of Caveolaementioning
confidence: 99%
“…AC1 and AC8 are activated by Ca 2ϩ in a calmodulin-dependent manner, whereas AC5 and AC6 are inhibited by Ca 2ϩ , independently of calmodulin (6). Accumulating evidence from heterologous expression studies is beginning to suggest that Ca 2ϩ -sensitive ACs (specifically AC5, AC6, and AC8) are enriched in lipid rafts, whereas Ca 2ϩ -insensitive ACs (AC2, AC4, and AC7) (4,7,8) are excluded from rafts and reside in the bulk PM. This differential localization may be directly related to specific properties of AC regulation, since the residence of Ca 2ϩ -regulatable ACs in lipid rafts is crucial for their responsiveness to physiological elevations in cytosolic Ca 2ϩ .…”
mentioning
confidence: 99%